Problématique suicidaire en agriculture : une difficile évaluation - Philippe Spoljar (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents a summary of the current situation of the evaluations of suicide among agriculture sector workers in France. We then examine the difficulties involved in conducting a classical epidemiological characterization of approaches to suicide risk prevention. Agricultural work studies often put forward various series of "risk factors", reinforcing the idea that their quantitative accumulation leads to psychiatric decompensation, without sufficiently taking into account other, often qualitative causal factors. We notice that these necessary investigations remain incomplete in their research, static in their approach, and contradictory in their results. They would be more comprehensive if more elaborate analyses focusing on fragilization and disconnect were conducted.